Changes in Western European banking - Gardener, Edward P. M.; Molyneux, Philip (London ; New York : Routledge, 1993)
Introduction. Current trends in banking and financial systems. Structure and performance. Monetary regulation, 1992 and supervision. Changes in balance sheet structure. Retail banking...
Keywords: Finance; Economics; Banks; Europe; Banks and banking -- Europe; Banks and banking, Foreign -- Europe; Banks and banking, International -- Europe; Monetary policy -- Europe